Sensory features in autism: Findings from a large population‐based surveillance system - Kirby, Anne V.; Bilder, Deborah A.; Wiggins, Lisa D.; Hughes, Michelle M.; Davis, John; Hall‐Lande, Jennifer A.; Lee, Li‐Ching; McMahon, William M.; Bakian, Amanda V. (Autism research, 2022)
Sensory features (i.e., atypical responses to sensory stimuli) are included in the current diagnostic criteria for autism spectrum disorder. Yet, large population‐based studies have not examined these features. This study aimed to determine the prevalence of sensory features among autistic children, and examine associations between sensory features, demographics, and co‐occurring problems in other areas. Analysis for this study included a sample comprised of 25,627 four‐ or eight‐year‐old autistic children identified through the multistate Autism and Developmental Disabilities Monitoring Network (2006–2014). We calculated the prevalence of sensory features and applied multilevel logistic regression modeling. The majority (74%; 95% confidence interval: 73.5%–74.5%) of the children studied had documented sensory features. In a multivariable model, children who were male and those whose mothers had more years of education had higher odds of documented sensory features. Children from several racial and ethnic minority groups had lower odds of documented sensory features than White, non‐Hispanic children. Cognitive problems were not significantly related to sensory features. Problems related to adaptive behavior, emotional states, aggression, attention, fear, motor development, eating, and sleeping were associated with higher odds of having documented sensory features. Results from a large, population‐based sample indicate a high prevalence of sensory features in autistic children, as well as relationships between sensory features and co‐occurring problems. This study also pointed to potential disparities in the identification of sensory features, which should be examined in future research. Disparities should also be considered clinically to avoid reduced access to supports for sensory features and related functional problems. Lay Summary In a large, population‐based sample of 25,627 autistic children, 74% had documented differences in how they respond to sensation. We also identified significant associations of sensory features with adaptive behavior and problems in other domains. Sensory features were less common among girls, children of color, and children of mothers with fewer years of education, suggesting potential disparities in identification.